Do Global Uncertainty Factors Affect Islamic Banking Stability? Evidence from Indonesia - Angga Hergastyasmawan; Ellen D Oktanti Irianto; Sigit Hartoko; Lukmanul Hakim; Nur Rizqi Febriandika (Al-Tijary, 2026)
Growing global uncertainty increasingly challenges banking stability, particularly in emerging economies vulnerable to external economic and geopolitical shocks. Although Islamic commercial banks are considered more resilient under Sharia principles, evidence on how different dimensions of global uncertainty affect their stability remains limited. This study investigates the long-run and short-run effects of global uncertainty on Islamic Commercial bank stability in Indonesia during 2016–2025 using the Vector Error Correction Model (VECM). Global uncertainty is proxied by U.S. Economic Policy Uncertainty (EPU), U.S. Geopolitical Risk (GPR), and the CBOE Volatility Index (VIX), while interest rates, exchange rates, and inflation serve as domestic control variables. In the long run, EPU and GPR positively affect Islamic bank stability, whereas inflation has a significant negative effect. The volatility index, interest rates, and exchange rates are insignificant, and no variables significantly influence stability in the short run. These findings indicate gradual long-run adjustment to external shocks. This study demonstrates that global uncertainty affects Islamic bank stability through distinct transmission mechanisms, implying that regulators should strengthen macroprudential policies while Islamic banks should enhance long-term resilience against external shocks.